Nasally delivered interferon-λ protects mice against infection by SARS-CoV-2 variants including Omicron - Chong, Zhenlu; Karl, Courtney E.; Halfmann, Peter J.; Kawaoka, Yoshihiro; Winkler, Emma S.; Keeler, Shamus P.; Holtzman, Michael J.; Yu, Jinsheng; Diamond, Michael S. (Cell reports (Cambridge), 2022)
Although vaccines and monoclonal antibody countermeasures have reduced the morbidity and mortality associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, variants with constellations of mutations in the spike gene jeopardize their efficacy. Accordingly, antiviral interventions that are resistant to further virus evolution are needed. The host-derived cytokine interferon lambda (IFN-λ) has been proposed as a possible treatment based on studies in human coronavirus 2019 (COVID-19) patients. Here, we show that IFN-λ protects against SARS-CoV-2 B.1.351 (Beta) and B.1.1.529 (Omicron) variants in three strains of conventional and human ACE2 transgenic mice. Prophylaxis or therapy with nasally delivered IFN-λ2 limits infection of historical or variant SARS-CoV-2 strains in the upper and lower respiratory tracts without causing excessive inflammation. In the lung, IFN-λ is produced preferentially in epithelial cells and acts on radio-resistant cells to protect against SARS-CoV-2 infection. Thus, inhaled IFN-λ may have promise as a treatment for evolving SARS-CoV-2 variants that develop resistance to antibody-based countermeasures. [Display omitted] •IFN-λ protects mice against SARS-CoV-2 B.1.351- and B.1.1.529-variant infections•IFN-λ selectively induces antiviral genes without causing excess inflammation•IFN-λ is produced by lung epithelial cells via Mavs and Myd88 signaling pathways•Stromal cells mediate the antiviral effect of IFN-λ during SARS-CoV-2 infection Chong et al. show that intranasally delivered murine IFN-λ2 protects mice against historical, B.1.351 (Beta), and B.1.1.529 (Omicron) SARS-CoV-2 infection in the upper and lower respiratory tracts without excessive inflammation. In the lung, IFN-λ is produced mainly by epithelial cells and acts on stromal cells to protect against of SARS-CoV-2 infection.